Sari segala ubat: Borneo's medical manuscript - Ahmad, Farahani Erna; Mohd Shafri, Mohd Affendi (2018)
Malay medical manuscripts contain knowledge on medical philosophy, history, pharmaceutical practice and prescriptions used by the Malay over several centuries. Up to 2016, there were only 11 publications on Malays ancient medical literature. Hence, this study adds to the effort of reviving the value of Malay intellectual heritage for further medical research. The main interest in this study is Sari Segala Ubat, a Borneo Malay medical manuscript from early 19th century Pontianak. It documents the medical prescriptions of Tama, purportedly a royal physician to the Sultanate of Pontianak in West Kalimantan. This exploratory study found that the manuscript covers treatments for at least 51 physical health conditions in addition to spiritual illnesses. There are 17 single compound prescriptions, 87 compounded prescriptions and 27 spiritual healing methods used. Therapeutic methods involved oral consumption, external application and mantera. Both local and imported ingredients employed were used including several with specific Borneo connection such as bengkala, bulangan and tutang. The study sheds more light on the medical practice of the Malays at the turn of the 19th century Borneo, in particular the West Kalimantan region, and comparative analysis with other Malay medical texts and contemporary scientific literatures would be the next step in the data-mining of this text.